2023
DOI: 10.3389/fendo.2023.1126683
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of autoimmune thyroid disease after COVID-19: A single-center, prospective study

Abstract: IntroductionThyroid dysfunctions associated with SARS-CoV-2 acute infection have been extensively described since the beginning of COVID-19 pandemics. Conversely, few data are available on the occurrence of thyroid autoimmunity after COVID-19 resolution. We assessed the prevalence of autoimmune thyroid disease (ATD) and thyroid dysfunctions in COVID-19 survivors three months after hospital admission.Design and methodsSingle-center, prospective, observational, cohort study performed at ASST Papa Giovanni XXIII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…33 Consistent with our findings, among COVID-19 survivors, females had higher odds of having thyroid autoimmunity. 33 Gender differences have been welldescribed in ATD in both adult and paediatric populations, 35,36 however, mechanisms are yet to be understood.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…33 Consistent with our findings, among COVID-19 survivors, females had higher odds of having thyroid autoimmunity. 33 Gender differences have been welldescribed in ATD in both adult and paediatric populations, 35,36 however, mechanisms are yet to be understood.…”
Section: Resultssupporting
confidence: 90%
“…However, there have been reports on the effect of the pandemic and the virus on ATD. [32][33][34] A recent study from Italy found that the prevalence of thyroid autoimmunity, specifically TPO antibodies, was greater in COVID-19 survivors in comparison to controls matched for age and gender. 33 Consistent with our findings, among COVID-19 survivors, females had higher odds of having thyroid autoimmunity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations